Summer Habitat Preference of Beluga Whales (Delphinapterus Leucas) in Cook Inlet, Alaska - Goetz, Kimberly T. (2005)
The Cook Inlet beluga whale (Delphinapterus leucas) lives in a confined body of water and therefore is susceptible to physical, ecological, and anthropogenic stresses. With approximately 360 animals remaining in the population and ongoing efforts to increase development in the area, it is important to identify habitat preferences of these whales. Advances in technology and statistical methods allow the integration of Geographic Information Systems (GIS) and environmental science to understand species distribution and habitat preferences. The present study aims to identify summer habitat areas using GIS applications. In predicting beluga habitat, twelve years of on-effort survey data were analyzed using logistic regression and Classification and Regression Tree (CART) to determine the importance of 1) bathymetry, 2) mudflats, and 3) flow accumulation values. Results suggest that mudflats are a significant predictor of beluga whale distribution during the summer months. While the importance of flow accumulation varied between the two models, belugas preferred higher flow accumulation inlets overall. The logistic regression and CART models produced similar habitat regions in terms of calculated area and relative location to beluga sightings. The habitat models developed in this study will aid biologists and wildlife managers in meeting conservation goals and making future legislative decisions to prevent the further decline of Cook Inlet belugas.